Corporate governance effectiveness and firm performance in global crisis: evidence from GCC countries - Alshdaifat, Sajead Mowafaq; Abdul Hamid, Mohamad Ali; Ab Aziz, Noor Hidayah; Saidin, Saidatunur Fauzi; Alhasnawi, Mushtaq Yousif (Emerald Publishing, 2024)
Purpose: This study aims to examine the impact of corporate governance (CG) effectiveness measured by board and audit committee index on firm performance of nonfinancial listed firms in Gulf Cooperation Council (GCC) countries, pre- and during the global crisis of COVID-19. Design/methodology/approach: The analysis used 2,238 observations from nonfinancial firms listed on GCC countries' stock exchange, covering the period from 2017 to 2022, using a fixed effect panel regression model. The data for this study were manually collected from the annual reports of 373 GCC-listed firms. Findings: The results demonstrate that the board's effectiveness index has a positive influence solely on accounting-based performance (return on assets) pre- and during the COVID-19 crisis. However, in terms of audit committee effectiveness, the results show a positive impact on market-based performance (Tobin’s Q) both pre- and during the COVID-19 crisis. Additional analysis indicates that the effectiveness of both the board and audit committee is more notable in larger firms compared to smaller firms. Practical implications: This study is crucial for investors, regulators, managers and governments tackling the financial impacts of global crises like COVID-19. Its comprehensive evaluation of board and audit committee effectiveness guides policymakers and practitioners in enhancing CG for profit and wealth maximization. Originality/value: This study offers novel evidence detailing the impact of CG effectiveness on firm performance over an extended period, encompassing the COVID-19 period and using a comprehensive index. In addition, this study was conducted in a unique CG setting, focusing on six emerging GCC countries. © 2024, Emerald Publishing Limited.